The Swedish Web Version of the Quality of Recovery Scale Adapted for Use in a Mobile App: Prospective Psychometric Evaluation Study - Nilsson, Ulrica; Dahlberg, Karuna; Jaensson, Maria (JMIR Publications, 2017)
BackgroundThe 40-item Quality of Recovery (QoR-40) questionnaire is well validated for measuring self-assessed postoperative recovery. The Swedish version of the 40-item Quality of Recovery (QoR-40) has been developed into a Web-based questionnaire, the Swedish Web version of the Quality of Recovery (SwQoR) questionnaire, adapted for use in a mobile app, Recovery Assessment by Phone Points, or RAPP. ObjectiveThe aim of this study was to test the validity, reliability, responsiveness, and clinical acceptability and feasibility of SwQoR. MethodsWe conducted a prospective psychometric evaluation study including 494 patients aged ≥18 years undergoing day surgery at 4 different day-surgery departments in Sweden. SwQoR was completed daily on postoperative days 1 to 14. ResultsAll a priori hypotheses were confirmed, supporting convergent validity. There was excellent internal consistency (Cronbach alpha range .91-.93), split-half reliability (coefficient range .87-.93), and stability (ri=.99, 95% CI .96-.99; P<.001). Cohen d effect size was 1.00, with a standardized response mean of 1.2 and a percentage change from baseline of 59.1%. An exploratory factor analysis found 5 components explaining 57.8% of the total variance. We noted a floor effect only on postoperative day 14; we found no ceiling effect. ConclusionsSwQoR is valid, has excellent reliability and high responsiveness, and is clinically feasible for the systematic follow-up of patients' postoperative recovery.